Study on phase characteristics of heterostructure por-Ga2O3/GaAs - S. S. Kovachov; I. T. Bohdanov; D. S. Drozhcha; K. M. Tikhovod; V. V. Bondarenko; I. G. Kosogov; Ya. O. Suchikova (Хімія, фізика та технологія поверхні)
The synthesis and characterization of heterostructure por-Ga2O3/GaAs represent a crucial advancement in nanomaterials, particularly in optoelectronic applications. Employing a two-stage electrochemical etching methodology, this research has elucidated the precise conditions required to fabricate such a heterostructure. The initial stage involves etching monocrystalline gallium arsenide (GaAs) using an aqueous nitric acid solution as the electrolyte. This process is governed by the redox reactions at the crystal-electrolyte interface, where GaAs are partially oxidized and selectively etched.